2014
DOI: 10.2147/ndt.s65695
|View full text |Cite
|
Sign up to set email alerts
|

Acute lipopolysaccharide exposure facilitates epileptiform activity via enhanced excitatory synaptic transmission and neuronal excitability in vitro

Abstract: Growing evidence indicates brain inflammation has been involved in the genesis of seizures. However, the direct effect of acute inflammation on neuronal circuits is not well known. Lipopolysaccharide (LPS) has been used extensively to stimulate brain inflammatory responses both in vivo and in vitro. Here, we observed the contribution of inflammation induced by 10 μg/mL LPS to the excitability of neuronal circuits in acute hippocampal slices. When slices were incubated with LPS for 30 minutes, significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…IL‐1 β and IL‐6 are also involved in the modulation and maintenance of long‐term potentiation (LTP) in vivo (del Rey et al., ). Recent studies have suggested that TLR4/HMGB1 signaling may impact neuronal excitability by interacting with NMDA receptors (Balosso et al., ; Maroso et al., ), and LPS facilitates epileptiform activity in vitro by enhancing excitatory synaptic transmission and neuronal excitability (Gao et al., ). EtOH‐induced HMGB1 release is also associated with NOX2/NLRP1 inflammasome signaling, which represents a new mechanism of EtOH‐associated neuron injury (Wang et al., ).…”
Section: Neuroimmune Signaling and Neurotransmissionmentioning
confidence: 99%
“…IL‐1 β and IL‐6 are also involved in the modulation and maintenance of long‐term potentiation (LTP) in vivo (del Rey et al., ). Recent studies have suggested that TLR4/HMGB1 signaling may impact neuronal excitability by interacting with NMDA receptors (Balosso et al., ; Maroso et al., ), and LPS facilitates epileptiform activity in vitro by enhancing excitatory synaptic transmission and neuronal excitability (Gao et al., ). EtOH‐induced HMGB1 release is also associated with NOX2/NLRP1 inflammasome signaling, which represents a new mechanism of EtOH‐associated neuron injury (Wang et al., ).…”
Section: Neuroimmune Signaling and Neurotransmissionmentioning
confidence: 99%
“…; Gao et al . ). At the cellular level, acute application of LPS to hippocampal slices was reported to enhance the frequency of excitatory postsynaptic currents (EPSCs; Pascual et al .…”
Section: Introductionmentioning
confidence: 97%
“…) and to increase neuronal excitability (Gao et al . ). These two actions, cooperatively, may underlie LPS‐induced brain hyperexcitability.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations